A comparative judgement approach to the large-scale assessment of primary writing in England. Issue 1 (2nd January 2020) - Wheadon, Christopher; Barmby, Patrick; Christodoulou, Daisy; Henderson, Brian
ABSTRACT: Writing assessment is a key feature of most education systems, yet there are limitations with traditional methods of assessing writing involving rubrics. In contrast, comparative judgement appears to overcome the reliability issues that beset the assessment of performance assessment tasks. The approach presented here extends previous work on comparative judgement by directly involving teachers in a large number of schools in the judging of young pupils' writing. To ensure quality control the process incorporated a process of 'anchoring' that ensured that teachers could not artificially inflate their own pupils' scores. The approach was used to assess the writing of 55, 599 primary pupils in England in 2017–2018. Overall, the results showed that a comparative judgement approach to writing incorporating anchoring shows promise in providing a fair and robust large-scale method to assess writing.